Critical Synthesis Package: Brief Decision Support Analysis Tool (DSAT-10) - Lori Wagner (Association of American Medical Colleges, 2015)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the Brief Decision Support Analysis Tool (DSAT-10); and (2) copies of the DSAT-10 instrument in both English and French developed by Dawn Stacey, RN, MScN, PhD. The DSAT-10 instrument is an observational feedback tool for evaluating decisional support interactions between health care workers and patients. The DSAT-10 includes 16 items divided into five domains of: Decision-Making Status; Knowledge of Options, Risks, and Benefits; Values Associated with Outcomes of Options; Support from Others; and Commitment to Act. Raters use the measure by listening to a provider-patient encounter and then complete the DSAT-10 point grid, which has clearly delineated items/points. Definitions of the items are included for clarification and easy reference. Scores range from zero to ten, with higher scores indicating more decisional support being verbalized during the patient-provider interaction. The DSAT-10 was originally utilized to assess nursing student phone conversations with patients, which were taped and reviewed by educators. There is support, however, for use with a variety of learners in a variety of clinical scenarios. Although tools such as the DSAT-10 offer a somewhat schematic and very calculated approach, and physicians in clinical practice have reported that this adds an artificial barrier to genuine patient-centered communication and therefore creates a negative impact on the doctor-patient relationship, the DSAT-10 provides an excellent framework for feedback, and individual learners can be tracked for improvement.